2022-RA-1052-ESGO Low-risk endometrial cancer and no adjuvant treatment: do isolated tumor cells (ITC) have an effect on recurrence? An international multi-institutional comparative study between ITC and node-negative in sentinel lymph node biopsy. (20th October 2022) - Cucinella, Giuseppe; Schivardi, Gabriella; Zhou, Xun Clare; Alhilli, Mariam; Wallace, Sumer; Wohlmuth, Christoph; Baiocchi, Glauco; Tokgozoglu, Nedim; Raspagliesi, Francesco; Buda, Alessandro; Zanagnolo, Vanna; Zapardiel, Ignacio; et al.
Abstract : Introduction/Background: The prognostic value of isolated tumor cells (ITC) (≤0.2 mm) in sentinel lymph nodes (SLN) of patients with endometrial cancer (EC) is still unclear. This study compared the recurrence-free survival (RFS) of low-risk EC patients who received no adjuvant therapy, who underwent a SLN biopsy and were node-negative vs. those who had ITC. Methodology: Patients with SLN-ITC, between 2012 and 2019, were identified from 21 centers worldwide, while SLN-node-negative patients were identified from Mayo Clinic, Rochester, between 2013 and 2018 and served as a comparing group. Only patients with stage IA endometrioid histology, and low-risk profile (grade 1 or 2 endometroid and myometrial infiltration <50%) who did not receive adjuvant therapy were included. The primary outcome was non-vaginal recurrence (peritoneal, hematogenous, and lymphatic). Results: A total of 494 patients (42 ITC and 452 node-negative) were included. There were 15 recurrences and the overall median follow-up for patients without recurrence was 2.2 (IQR 1.1–3.0) years for the ITC group and 2.6 (IQR 0.6–4.2) years for the node-negative group. The presence of SLN-ITC (HR, 5.66; 95% CI, 1.76–18.23), LVSI (HR, 10.66 95% CI, 2.27–50.04) and grade 2 (HR, 3.16; 95% CI, 1.14–8.75) were significant risk factors for non-vaginal recurrence at univariate analysis. Non-vaginal RFS was significantly poorer for the ITC group (vs. node-negative) [p=0.001, figure 1, 4-year RFS: 88.2% (95% CI, 77.8–100) vs 96.9% (95% CI, 94.5–99.3)]. Furthermore, among those without LVSI (N=480), the presence of SLN-ITC (adjusted HR, 4.47; 95% CI, 1.21–16.60) was significantly associated with non-vaginal recurrence after adjusting for grade. Conclusion: Patients with SLN-ITC and a low-risk profile who received no adjuvant therapy had a worse prognosis than node-negative patients with similar risk factors after considering grade and LVSI. Longer follow-up is needed to confirm this finding.